1978
DOI: 10.1063/1.862083
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-three-dimensional turbulence in magnetized nonuniform plasma

Abstract: A simple nonlinear equation is derived to describe the pseudo-three-dimensional dynamics of a nonuniform magnetized plasma with Te≫Ti by taking into account the three-dimensional electron, but two-dimensional ion dynamics in the direction perpendicular to B0. The equation bears a close resemblance to the two-dimensional Navier–Stokes equation. A stationary spectrum in the frequency range of drift waves is obtained using this equation by assuming a coexisting large amplitude long wavelength mode. The ω-integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
532
2

Year Published

1981
1981
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 869 publications
(539 citation statements)
references
References 15 publications
5
532
2
Order By: Relevance
“…Accumulated evidence from many years of computer simulations has shown that they are important constituents of plasma microturbulence as well. This could be expected from the close analogy between Rossby waves and drift waves (Horton and Hasegawa, 1994), and indeed was anticipated by Hasegawa and Mima (1978). Zonal flows are theoretically interesting because they are nonlinearly driven and very weakly damped, and their self-generated (random) shear can be expected to play a role in the dynamics of the modes (which will be called drift waves for short) that drive them.…”
Section: Convective Cells Zonal Flows and Streamersmentioning
confidence: 99%
See 4 more Smart Citations
“…Accumulated evidence from many years of computer simulations has shown that they are important constituents of plasma microturbulence as well. This could be expected from the close analogy between Rossby waves and drift waves (Horton and Hasegawa, 1994), and indeed was anticipated by Hasegawa and Mima (1978). Zonal flows are theoretically interesting because they are nonlinearly driven and very weakly damped, and their self-generated (random) shear can be expected to play a role in the dynamics of the modes (which will be called drift waves for short) that drive them.…”
Section: Convective Cells Zonal Flows and Streamersmentioning
confidence: 99%
“…Although extensive research on the NSE in the presence of forcing and dissipation shows that actual turbulent steady states are far from equilibrium, statistical methods have made substantial inroads. A fundamental difficulty with the statistical approach is that nonlinear systems can also display a tendency toward self-organization (Hasegawa, 1985). Certain fluid equations admit the possibility of soliton solutions; in plasmas, the Vlasov equation can support Bernstein-Greene-Kruskal (BGK) modes (Bernstein et al, 1957).…”
Section: Nonlinear Dynamics and Statistical Descriptionsmentioning
confidence: 99%
See 3 more Smart Citations